The principle of transparency in the Ukrainian cecentralisation reform - Slukhai, Sergii (Central European Public Administration Review, 2019)
After the revolution of dignity (2013-2014), the new Ukrainian government set out a number of reforms, one of which - and a successful one so far - was decentralisation, involving territorial amalgamation and re-allocation of public revenues and outlays in favour of the newly-established amalgamated territorial communities (ATCs). This study aims to analyse whether decentralisation is supported by the realisation of the budget transparency principle. We attempt to fill the gap still existing in the research of public sector transparency in Ukraine, concerning the basic administrative level, hereby being limited to big cities and regions. The authors carried out an assessment of budget transparency in newly-established ATCs in four Ukrainian regions by applying a simplified methodology 'snapshot assessment') involving 11 measures that could be easily located on the ATC websites. In order to understand the reasons for a particular level of transparency, a polling of ATC heads was undertaken. The findings of the study demonstrate that the overall budget transparency in the newly established ATCs is rather low and subject to significant interregional variation. We find that the local officials overstate the existing level of budget transparency in their communities and are not proactive in their efforts to raise it. The importance of this article lies in substantiating the need for making budget transparency a priority for local officials, as well as in detailing the activity of the state and the local community in this field.
Keywords: amalgamated territorial community; decentralisation; fiscal transparency; Ukraine